Prevalence and Death Rate of COVID-19 in Autoimmune Systemic Diseases in the First Three Pandemic Waves. Relationship with Disease Subgroups and Ongoing Therapies - Ferri, Clodoveo; Raimondo, Vincenzo; Gragnani, Laura; Giuggioli, Dilia; Dagna, Lorenzo; Tavoni, Antonio; Ursini, Francesco; L'Andolina, Massimo; Caso, Francesco; Ruscitti, Piero; Caminiti, Maurizio; Foti, Rosario; et al. (Current Pharmaceutical Design, 2022)
Objective: Autoimmune systemic diseases (ASD) represent a predisposing condition to COVID-19. Our prospective, observational multicenter telephone survey study aimed to investigate the prevalence, prognostic factors, and outcomes of COVID-19 in Italian ASD patients. Methods: The study included 3,918 ASD pts (815 M, 3103 F; mean age 59±12SD years) consecutively recruited between March 2020 and May 2021 at the 36 referral centers of COVID-19 and ASD Italian Study Group. The possible development of COVID-19 was recorded by means of a telephone survey using a standardized symptom assessment questionnaire. Results: ASD patients showed a significantly higher prevalence of COVID-19 (8.37% vs. 6.49%; p<0.0001) but a death rate statistically comparable to the Italian general population (3.65% vs. 2.95%). Among the 328 ASD patients developing COVID-19, 17% needed hospitalization, while mild-moderate manifestations were observed in 83% of cases. Moreover, 12/57 hospitalized patients died due to severe interstitial pneumonia and/or cardiovascular events; systemic sclerosis (SSc) patients showed a significantly higher COVID-19-related death rate compared to the general population (6.29% vs. 2.95%; p=0.018). Major adverse prognostic factors to develop COVID-19 were: older age, male gender, SSc, pre-existing ASD-related interstitial lung involvement, and long-term steroid treatment. Of note, patients treated with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) showed a significantly lower prevalence of COVID-19 compared to those without (3.58% vs. 46.99%; p=0.000), as well as the SSc patients treated with low dose aspirin (with 5.57% vs. without 27.84%; p=0.000). Conclusion: During the first three pandemic waves, ASD patients showed a death rate comparable to the general population despite the significantly higher prevalence of COVID-19. A significantly increased COVID-19- related mortality was recorded in only SSc patients’ subgroup, possibly favored by preexisting lung fibrosis. Moreover, ongoing long-term treatment with csDMARDs in ASD might usefully contribute to the generally positive outcomes of this frail patients’ population.
Keywords: aspirin